MicroRNA-205-5p Targets HMGB1 to Suppress Inflammatory Responses during Lung Injury after Hip Fracture. (28th November 2019) - Yu, Xiaojie; Chen, Xiaobin; Sun, Tiansheng
Abstract : Hip fracture is the most common type of injury in elderly people and is associated with a high incidence of complications and risk of mortality. In these patients, subsequent pulmonary infection can contribute to the development of an acute lung injury, a consequence of the systemic inflammatory response induced by hip fracture. Although the crucial role of microRNAs (miRNAs) in inflammatory responses has been established, the functions of miRNAs in the inflammatory responses associated with lung injury after hip fracture remain poorly understood. In this study, we explored the potential role of miR-205-5p in lung injury after hip fracture in an in vivo hip fracture model and in vitro cultures of human pulmonary alveolar epithelial cells (HPAEpiC). An analysis of clinical serum samples revealed increased levels of miR-205-5p and high mobility group box 1 (HMGB1) after hip fracture. A bioinformatics analysis and dual-luciferase reporter assay identified HMGB1 as a potential target of miR-205-5p. The overexpression of miR-205-5p clearly reduced the expression of HMGB1 and inhibited NF- κ B signaling, apoptosis, and proinflammatory cytokine production while enabling continued cell proliferation. Our results demonstrate that the upregulation of miR-205-5p suppresses inflammatory responses and promotes cell viability and proliferation by selectively targeting HMGB1 in the context of lung injury after hip fracture. Therefore, miR-205-5p may be an alternative target of therapeutic strategies for lung injury after hip fracture.